Brown marmorated stink bug, Halyomorpha halys (Hemiptera: Pentatomidae), detections in Western Sydney, New South Wales, Australia. Issue 4 (4th September 2019) - Horwood, Martin; Milnes, Joshua M; Cooper, W Rodney
Abstract: Brown marmorated stink bug (BMSB), Halyomorpha halys Stål, 1855, is a polyphagous agricultural insect pest which causes serious production losses. BMSB also has human lifestyle impacts which arise from its habit of overwintering in homes. The invasiveness of BMSB and the harm it causes is making it a pest of increasing global importance. Over the past 30 years, the bug has spread from its native range in East Asia to North America and Europe. On November 2017 and January 2018, BMSBs were found at two Western Sydney locations in goods imported from northern Italy. While BMSB detections in imports are common in Australia, these encounters were significant because of sightings of bugs outside the infested premises, indicating possible spread into the local environment. Measures undertaken in Western Sydney to contain and eradicate BMSB included fumigation of infested goods, insecticide treatment of the warehouse site and surroundings and delimiting surveillance. Before commencing widespread surveillance, a vegetation survey was conducted to identify known host and potential BMSB host plants around the infested premises. ESRI Collector for ArcGIS™ was used to compile host plant location data which served as the basis for pheromone trap deployment and physical inspection. Surveillance continued until May 2018. No live BMSBs were detected. DNA analysis of dead BMSBs collected from infested goods discerned the presence of two different haplotypes (H): H1 (previously detected in North America, Europe and China) and H23 (North America and Japan).